Neocyphon, a new genus of New World marsh beetles closely related to Contacyphon Gozis (Coleoptera: Scirtidae) - Ruta, Rafał; Libonatti, María Laura; Epler, J. H.; Klausnitzer, Bernhard (Zootaxa, 2026)
Neocyphon gen. nov. is proposed to accommodate species previously described in Contacyphon Gozis, 1886: Neocyphon corumbanus (Pic, 1941) comb. nov., Neocyphon guatemalensis (Champion, 1897) comb. nov., and Neocyphon humberti (Pic, 1918) comb. nov., and 10 new species: Neocyphon diiorioi sp. nov. (Brazil, Paraguay), Neocyphon ecuadorensis sp. nov. (Ecuador), Neocyphon guianensis sp. nov. (French Guiana), Neocyphon lojaensis sp. nov. (Ecuador), Neocyphon mesopotamicus sp. nov. (Argentina, Brazil, Paraguay), Neocyphon peruvianus sp. nov . (Peru), Neocyphon platensis sp. nov. (Argentina, Uruguay), Neocyphon pseudoplatensis sp. nov. (Argentina), Neocyphon ratzlaffi sp. nov. (The Bahamas, Cayman Islands, Cuba, Dominican Republic, USA), and Neocyphon teresopolisensis sp. nov. (Brazil). Neocyphon is a predominantly Neotropical genus ranging from Florida in the north to central and northern Argentina in the south. Two species groups are distinguished, differing in details of structural anatomy of male and female genitalia.